Development Of A Control Model For A Head On Collision Avoidance System - Ngo, Shi Hui (Universiti Sains Malaysia, 2022)
Overtaking is one of the most serious causes of accidents on two-lane two-way roads. Collisions with oncoming vehicles are account for 42% of the largest group. Collisions with oncoming vehicles can also be known as head-on collisions where the front ends of two vehicles hit each other in opposite directions. Safety is the most important issue while driving. Most traffic accidents occur because of an insufficient safe distance. In this paper, an overtaking safety system which can dynamically adjust the safe following distance between vehicles depending on the speed has been proposed. This system can be used to determine and maintain safe following distances both in front and rear of a car. The passenger car and the flying overtaking strategy will be used to simulate the overtaking scenario. With this proposed system, the safe longitudinal distance between the overtaking and oncoming vehicles can be calculated to make sure that the overtaking manoeuvre can be performed successfully to avoid head-on collision.